The Changes of Serum Leptin and Kisspeptin Levels in Chinese Children and Adolescents in Different Pubertal Stages - Hui juan Zhu; Su juan Li; Hui Pan; Naishi Li; Dian xi Zhang; Lin jie Wang; Hong bo Yang; Qinyong Wu; Feng ying Gong (International Journal of Endocrinology)
The aim of the study is to investigate the changes of serum leptin and kisspeptin levels in children and adolescents with different pubertal stages and nutritional states. A total of 647 Chinese children and adolescents were recruited, and serum estradiol, testosterone, pituitary gonadotropins, leptin, and kisspeptin levels were measured. The results showed that serum leptin levels of boys in T2 stage were the highest among the five stages, while they showed a gradual increase from T1 to T5 stage in girls and reached the highest in T5 stage (P<0.05). Conversely, serum kisspeptin levels of boys were higher in T4 and T5 stages than those in T1 stage, while its levels of girls were the highest in T2 stage, 21.4% higher than those in T1 stage (P<0.05). Both leptin and kisspeptin levels were positively correlated with BMI, WC, and weight in all boys and girls (all P<0.05). In conclusion, kisspeptin levels were firstly found to be notably changed in pubertal stages and nutritional status in Chinese children and adolescents with a significant sexual dimorphism. Obese/overweight girls had higher kisspeptin levels, and there was a positive correlation between kisspeptin and FSH and LH and obesity-related parameters in all boys and girls.